Pengaruh Waktu Penyimpanan Larutan Oral Nutraceutical Ekstrak Bunga Delima Merah (Punica granatum L.) Terhadap Perubahan Hambatan Pertumbuhan Escherichia coli (In Vitro) - Nirwana Dewanty, Shitras, drg. Mahmud Kholifa, MDSc (2017)
Escherichia coli is normal flora in oral cavity can cause infections in the digestive tract, it is necessary for preventing and medication using oral solution nutraceuticals products that are used as gargled and safe if swallowed because it is made of bioactive compounds that have antibacterial substances such as red pomegranate flower extract and chemicals that are prevalent in food and beverage products. By controlling factors such as temperature, light, and humidity to maintain its quality, red pomegranate flower extract nutraceutical oral solution extract is stored in climate chamber for 28 days. from natural materials with antibacterial effects such as red pomegranate flower. Oral nutraceutical is stored by controlling for factors such as temperature, light, and moisture to maintain its quality. This study aims to determine the effect of storage time of oral solution nutraceutical red pomegranate flower extract toward the changes in growth inhibition of Escherichia coli. This study was an experimental study with post test only control group design with method by measuring the diameter of clear zone on a petri dish with the addition of red pomegranate flower extract nutraceutical oral solution that have not been stored, stored for 7 days, stored for 14 days, stored for 21 days, stored for 28 days. The results showed an average diameter of clear zone with nutraceutical oral solution has not been saved, stored 7 days, stored for 14 days, stored for 21 days, stored for 28 days respectively 3,32mm, 2,87mm, 2,85mm, 2,46mm , 2,39mm. The result of one way ANOVA tested p = 0.038 (p <0.05). Post Hoc LSD test showed a p-value <0.05 after 14 days of storage, the storage time of nutraceutical oral solution of red pomegranate flower extract (Punica granatum L.) not significantly effecting the changes of Escherichia coli growth inhibition in 14 days.